Effects of practice on visual finger-force control in children at risk of developmental coordination disorder - Diz, Maria Angélica da Rocha [UNESP]; Ferracioli, Marcela de Castro; Hiraga, Cynthia Yukiko [UNESP]; Oliveira, Marcio Alves de; Pellegrini, Ana Maria [UNESP] (Elsevier, 2018)
Background: The production of finger force control is essential for a large number of daily activities. There is evidence that deficits in the mechanisms of accuracy and control of finger force tasks are associated with children's motor difficulties. Objective: To compare the effect of practice of an isometric finger force/torque task between children with significant movement difficulty and those with no difficulty movement. Methods: Twenty-four children aged between 9 and 10 years (12 at risk of developmental coordination disorder and 12 with no movement difficulty – typically developing children) were asked to produce finger force/torque control in a continuous and constant 25% of maximum voluntary torque with visual feedback during 15 s. Practice was given during five consecutive days with 15 trials per day. After the practice with visual feedback, children were asked to perform five trials without visual feedback. In these trials, feedback was removed 5 s after the start of the trial. Results: Typically developing children were consistently more accurate in maintaining finger force/torque control than those children at risk of developmental coordination disorder. Children from both groups improved the performance in the task according to practice sessions. Also, children at risk of developmental coordination disorder poorly performed the task without visual feedback as they did when visual feedback was available. Conclusion: The present study give support to the idea that movement difficulty is associated with finger force/torque control and children at risk of developmental coordination disorder can improve finger force/torque control with practice when visual feedback is available.
Keywords: DCD; Fine-tune; Isometric torque; Practice